(untitled) (Information systems and technologies security, 2025)
B a c k g r o u n d . In recent years, the level of cybercrime has grown rapidly. The complexity and diversity of these threats has forced organizations to prioritize advanced cybersecurity solutions, including the use of artificial intelligence technologies that can quickly analyze data to identify potential threats and anomalies. By 2027, the AI-based cybersecurity market is expected to exceed 46 billion. However, as AI strengthens and refines defenses, cybercriminals are adapting by exploiting vulnerabilities and even using AI to enhance attacks. This dual use of AI underscores the need for balanced and intelligent strategies that combine the predictable capabilities of AI with human knowledge and talent. M e t h o d s . My Research highlights effective risk prevention strategies, including promoting a security-aware culture, implementing strong passwords and two-factor authentication, regularly assessing and updating systems, enhancing firewalls, and adhering to cybersecurity regulations. AI proves valuable in threat detection and response, giving companies a competitive edge, though it raises concerns about reducing human roles in security tasks. R e s u l t s . The research indicates that AI positively impacts cybersecurity by enabling faster detection and response to threats, allowing organizations to proactively identify and address vulnerabilities. Companies that integrate AI into their cybersecurity strategies gain an advantage in managing complex cyber threats. However, concerns persist about AI’s dual-use nature, as it could also be leveraged by cybercriminals for advanced attacks. This potential for AI to operate independently raises questions about the diminishing role of human oversight. Ultimately, the findings stress the need for a balanced approach: while AI is essential for modern cybersecurity, human involvement remains crucial. Continuous adaptation and a blend of technological and human expertise are necessary to protect critical infrastructure and data. C o n c l u s i o n s . To summarise, the rapid growth of cybercrime underscores the necessity for robust cybersecurity measures to protect sensitive information and ensure operational integrity. Artificial Intelligence is becoming crucial in enhancing cybersecurity through advanced threat detection, pattern recognition, and predictive analysis. While AI offers significant benefits, it can also be exploited by cybercriminals, highlighting the importance of vigilance and innovation in security strategies. Despite advancements in AI, human expertise remains vital for interpreting insights, making informed decisions, and adapting to new threats. A multi-faceted approach, including employee training, regular audits, and strong data protection, is essential for effective cybersecurity. Enhanced cooperation among organizations, governments, and international partners is crucial for developing effective strategies to combat cybercrime. Continued research into AI capabilities and ethical considerations is necessary to address the evolving landscape of cybersecurity threats.